Policy analysis and environmental problems at different scales: asking the right questions - Tomich, Thomas P.; Chomitz, K.; Francisco, H.; Izac, N.A.; Murdiyarso, Daniel; Ratnere, B.D.; Thomas, D.E.; Noordwijk, Meine van (2004)
This article discuss a search for a common understanding of three environmental problems linked to land use change in Southeast Asia: smoke pollution, degradation of biodiversity functions, and degradation of watershed functions. The objectives of this special issue are to identify usable data and methods for quantifying the impact of land use change on these environmental problems, to identify gaps in either data or methods and, where gaps exist, to set priorities for filling them. That assessment will be done in greater detail in the conclusion part. In this paper, it begins the process by raising policy analysts’ basic questions for each environmental problem in turn and making a preliminary assessment of where each of these three problems lies in the ‘environmental issue cycle’.